2021
DOI: 10.21203/rs.3.rs-382781/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The characteristics of proteome and metabolome associated with contrasting sperm motility in goat seminal plasma

Abstract: Sperm motility is an index tightly associated with male fertility. A close relationship between seminal plasma and sperm motility has been confirmed. This study was to assess the protein and metabolite profiles of seminal plasma obtained from adult goats with high or low sperm motility using the proteomic and metabolomic strategies. In total, 2098 proteins were found. 449 differentially expressed proteins (DEPs) were identified, and 175 DEPs were enriched in the high motility group. The obtained DEPs primarily… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…A possible reason for such phenomenon could be to the interactions of these proteins with epididymal fluids during maturation and at ejaculation. Evidence has shown that a wide variety of sperm proteins are expressed in high levels in the bovine, goat, boar, and canine SP [11,12,26,43]. It was suggested that proteins occurring in both sperm and SP proteome could be due to non-specific aggregation of spermatozoa and SP proteins or might indicate an active and/or protein transport mechanism between the sperm cells and SP [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible reason for such phenomenon could be to the interactions of these proteins with epididymal fluids during maturation and at ejaculation. Evidence has shown that a wide variety of sperm proteins are expressed in high levels in the bovine, goat, boar, and canine SP [11,12,26,43]. It was suggested that proteins occurring in both sperm and SP proteome could be due to non-specific aggregation of spermatozoa and SP proteins or might indicate an active and/or protein transport mechanism between the sperm cells and SP [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that proteins occurring in both sperm and SP proteome could be due to non-specific aggregation of spermatozoa and SP proteins or might indicate an active and/or protein transport mechanism between the sperm cells and SP [43,44]. In different animal species, it has been confirmed that the SP comprises a diverse set of protein components, which bind to spermatozoa and affect their membrane structure and fertilizing ability [8,9,11,12,26]. Moreover, SP proteins also affect the physiology of the female reproductive tract, influencing the immune and inflammatory response processes, and embryo development [9,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations